Pengukuran Maturity Level E-Learning - Nurva Widia; Idria Maita (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Maturity Level is a method of the COBIT Framework (Control Objectivitas for Information and Related Technology that can measure the maturity level of the scale of a system. Utilization of information technology such as E-learning can enhance the effectiveness and flexibility in teaching and learning, By measuring the maturity level at E Labor-Learning in vocational Guidance and Counseling University of Riau Patronage, can help users and management with effective decision making to overcome the problems that occur, and can control the use of information technology that supports the use of E-learning. So it can achieve the expected goals based on strategic plans and recommendations obtained from the measurements of the level of maturity level.Keywords: E-learning, Framework COBIT, Maturity Level